Understanding the human conflict processing network: A review of the literature on direct neural recordings during performance of a modified stroop task - Ryan S. Chung; Jonathon Cavaleri; Shivani Sundaram; Zachary D. Gilbert; Roberto Martin Del Campo-Vera; Andrea Leonor; Austin M. Tang; Kuang-Hsuan Chen; Rinu Sebastian; Arthur Shao; Alexandra Kammen; Emiliano Tabarsi; et al. (Neuroscience Research, 2024)
The Stroop Task is a well-known neuropsychological task developed to investigate conflict processing in the human brain. Our group has utilized direct intracranial neural recordings in various brain regions during performance of a modified color-word Stroop Task to gain a mechanistic understanding of non-emotional human conflict processing. The purpose of this review article is to: 1) synthesize our own studies into a model of human conflict processing, 2) review the current literature on the Stroop Task and other conflict tasks to put our research in context, and 3) describe how these studies define a network in conflict processing. The figures presented are reprinted from our prior publications and key publications referenced in the manuscript. We summarize all studies to date that employ invasive intracranial recordings in humans during performance of conflict-inducing tasks. For our own studies, we analyzed local field potentials (LFPs) from patients with implanted stereotactic electroencephalography (SEEG) electrodes, and we observed intracortical oscillation patterns as well as intercortical temporal relationships in the hippocampus, amygdala, and orbitofrontal cortex (OFC) during the cue-processing phase of a modified Stroop Task. Our findings suggest that non-emotional human conflict processing involves modulation across multiple frequency bands within and between brain structures.